2020
DOI: 10.1177/1055665620946184
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Survey Outcomes in Cleft Surgeons and Orthodontists

Abstract: Objective: Determine prevalence and characteristics of musculoskeletal pain and pathology in cleft providers. Design: An IRB-exempt survey based on previously validated surveys was administered. Data collected included demographics, practice description, musculoskeletal pain history, formal diagnoses, and interventions. Setting: Survey was sent to all cleft centers approved by the American Cleft Palate-Craniofacial Association worldwide. Patients, Participants: All cleft surgeons and orthodontists at these cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…26 Kim et al founded that the most common pain zones of the cleft surgeons and orthodontists were the neck (71.2%), shoulders (52.5%), and lower back (67.8%). 27 Similar to our study, most trials about pain areas and quality of life in healthcare personnel revealed that low back and neck pain was high. Dentists mainly were preferred as the working group in these studies.…”
Section: Discussionsupporting
confidence: 89%
“…26 Kim et al founded that the most common pain zones of the cleft surgeons and orthodontists were the neck (71.2%), shoulders (52.5%), and lower back (67.8%). 27 Similar to our study, most trials about pain areas and quality of life in healthcare personnel revealed that low back and neck pain was high. Dentists mainly were preferred as the working group in these studies.…”
Section: Discussionsupporting
confidence: 89%
“…Exclusion of these 12 trials may have precluded certain comparisons from achieving significance. Although the majority of the musculoskeletal literature has centered around back and neck discomfort, [49][50][51][52] it is possible the pain reported by surgeons within our cohort was derived from joint angles or body portions not analyzed by the present study. Lastly, as subjects were outfitted with sensors, participants may have been subject to the Hawthorne effect, where participants' awareness of the sensors resulted in more vigilant or altered posture.…”
Section: Discussionmentioning
confidence: 99%